The Anthropology of Islam: By Gabriele Marranci (Oxford and New York: Berg, 2008. 182 pages.) (American Journal of Islam and Society, 2008)
Gabriele Marranci’s latest book, The Anthropology of Islam, examines thehistory and current status of anthropological work focusing on Islam.Despite its title, this work seems less intended as an overview of the anthropologyof Islamthan as a critique of the field. Essentialism,Marranci argues,still marks prominent works of anthropology that focus onMuslims. EdwardSaid’s critique of Orientalism and anthropology’s post-1980s “crisis of representation”notwithstanding, Islam and Muslims are still represented inmany anthropological texts as fixed and unchanging, tethered to an imagined,unitary tradition. Anthropological studies have not yet caught up withthe impact of migration, the Internet, or other global processes, and thus theyrepresent Muslims abroad as caught between cultures or locked in aninevitable crisis of identity in which a rigidly defined faith is found to be atodds with the pluralism of western life.The approach Marranci advocates involves examining the diverse waysMuslims feel and experience their religion, as well as the complex networksand interactions in which they locate themselves, particularly in the West.“‘Muslim,’” he writes, “has an emotional component attached to it. Theyfeel to be Muslim. Then, and only then, the ‘feeling to be’ is rationalized,rhetoricized, and symbolized, exchanged, discussed, ritualized, orthodoxizedor orthopraxized” (p. 8). Drawing on cognitive neuroscience, the authoradvocates exploring identity practices through this “feeling to be” Muslim ...